Use and Challenges of ICT in Rural Development in Nepal (A Case Study of Bagmati Rural Municipality of Lalitpur, Ward: 1) - Bhattarai, Nabaraj; Sunuwar, Man Bahadur; Thapa, Keshav; Khadka, Subardhan (BARUN Journal, 2026)
Information communication technology ("ICT) is the broad range of technologies that facilitate communication and the processing and transmission of information through electronic means, including computing, telecommunications, and digital media. Main purpose of this study is to analyze the use and challenge of ICT in Rural Development in Nepal (A case study of Bagmati Rural Municipality of Lalitpur, Ward -1). Out of total population, 140 ICT users were direct interviewed with purposive non-probability sampling method applying the pre-structured questionnaires. Descriptive research design, Quantitative research method was applied for the whole process. Both primary and secondary data have been used. The primary data were collected through direct interview to the potential respondents and secondary data were collected through different published and non-published national and international publications i.e. Journal, books, scholarly articles, google articles, reports of government offices etc. Out of 140 respondents, almost all are using the ICT. ICT is being their life line. ICT is milestone of the rural development. They are using ICT in almost in all areas, agriculture, business, service, marketing. Individual people are highly benefited from the ICT in the grass root level.